2009
DOI: 10.1177/145749690909800303
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation of Endoscopicallyplaced Self-Expanding Metallic Stents in Patients with Acute Large Bowel Obstruction

Abstract: Background and Aims: self-expanding metallic stents (sems) have since 1991 established themselves as an option in the treatment of large bowel obstruction. the aim of this study was to evaluate the use of sems in management of acute colorectal obstructions at a danish surgical gastroenterology center. Material and Methods: retrospective review of charts from all patients who, in the period marts 2002 to december 2007 underwent insertion of as ems for an acute large bowel obstruction.Results: of 45 patients inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…There is limited data on longterm follow-up and randomised studies do not exist. Many of the studies are case reports or the study populations are small [8][9][10][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. At the time of writing this report, the biggest series of patients treated with SEMS due to benign obstruction is 23 patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on longterm follow-up and randomised studies do not exist. Many of the studies are case reports or the study populations are small [8][9][10][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. At the time of writing this report, the biggest series of patients treated with SEMS due to benign obstruction is 23 patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…The use of SES for the management of benign obstruction in the oesophagus and biliary system has been reported, with variable results [8,9]. Benign obstruction in the colon and rectum managed by SES has recently been investigated by a number of case series [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This systematic review will report the efficacy and safety outcomes following endoscopic placement of SES for benign colorectal obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Acute large-bowel obstruction represents a surgical emergency; in 85 % of cases, it is caused by the presence of a colorectal tumor ( 1 ). It has been reported that ~ 15 -20 % of patients with colorectal cancer present with an emergent obstruction of the large bowel at the time of diagnosis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%